2011
DOI: 10.1159/000324232
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Influenza AH1N1 Infections in a Neonatal Unit in Spain

Abstract: We describe three positive influenza AH1N1 cases in a neonatal unit during the influenza pandemic in Spain. One term baby presented with an upper respiratory tract infection, another preterm infant with an apnea episode following nosocomial infection, and thirdly, a term infant of a mother with influenza AH1N1 had severe respiratory distress and pneumothoraces needing high-frequency ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Very little is known about their role in neonatal units, 4,5 although we have demonstrated that they are associated with relevant pathology in our unit. 6,7 Neonatal units devote considerable effort to set up measures to prevent infection, such as the use of hygiene measures of proved effectiveness by any staff that comes in contact with the infants: applying alcohol gel before and after manipulating the child, wearing gloves, frequent handwashing, prevention of catheter-related sepsis by monitoring the catheter and withdrawing it as early as possible, and the prudent use of antibiotics.…”
Section: Infecciones Virales De Las Vías Respiratorias En La Unidad Dmentioning
confidence: 99%
“…Very little is known about their role in neonatal units, 4,5 although we have demonstrated that they are associated with relevant pathology in our unit. 6,7 Neonatal units devote considerable effort to set up measures to prevent infection, such as the use of hygiene measures of proved effectiveness by any staff that comes in contact with the infants: applying alcohol gel before and after manipulating the child, wearing gloves, frequent handwashing, prevention of catheter-related sepsis by monitoring the catheter and withdrawing it as early as possible, and the prudent use of antibiotics.…”
Section: Infecciones Virales De Las Vías Respiratorias En La Unidad Dmentioning
confidence: 99%
“…Information about the prevalence of VRI in surveillance studies in NICUs varies from 2% to 55% among the screened infants, 1–4 and these studies have emphasized the importance of these viruses in the respiratory morbidity of the newborn. In addition to the classic viral outbreaks caused by respiratory syncytial virus (RSV) or influenza, 5,6 rhinovirus (hRV) or adenovirus (hAD) 1,4,7 are particularly relevant. hRV is the viral species causing VRI most frequently identified in preterm infants and associates increased respiratory support, longer hospital stay, and higher rates of bronchopulmonary dysplasia (BPD) 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Además de los virus clásicos, como el VRS y los virus de la gripe, los rinovirus (RV), metapneumovirus humano (hMPV), coronavirus (CoV) y bocavirus humano (hBoV) desempeñan un papel cada vez más importante en las infecciones respiratorias de los lactantes. No se conoce prácticamente nada sobre su papel en unidades neonatales 4,5 , si bien nosotros hemos objetivado que se asocian con patología relevante en nuestra unidad 6,7 .…”
Section: Introductionunclassified